Clinicomycological study of tinea infections in and around Pune - Dhayagude, Snehal; Arjunwadkar, Vidya; Chavan, Ravindranath; Bharadwaj, Renu; Kagal, Anju (International Journal of Research in Dermatology, 2019)
Background: Tinea is a common fungal infection seen in the tropical and subtropical countries affecting the skin and its appendages. The presentation may vary from mild scaling to severe inflammation with bacterial super infection. It may be confused with other manifestation such as psoriasis, seborrhea, drug eruptions, eczema, and contact dermatitis. Hence correct diagnosis is necessary for appropriate treatment, which will reduce morbidity, discomfort and lessens possibility of transmissions. The aims and objectives were to determine clinicomycological profile of Tinea infections in patients attending dermatology OPD of B. J. Govt. Medical College and Sassoon General Hospital, Pune. Methods: Skin scrapings, nail clippings; hair samples from clinically suspected cases of tinea were collected. Identification of dermatophytes from these samples was done by conventional technique. Results: 119 clinically suspected cases of Tinea infections were processed over a period of one year. Out of these cases mixed infection of Tinea cruris with corporis was the predominant (27.73%) clinical presentation. Among all the samples, fungal filaments were seen by KOH mount in 48 (40.33%) whereas 35 (29.41%) samples were confirmed as dermatophytes by culture. Among these 35 isolates of dermatophytes 20 were T. rubrum, 7 isolates were T. tonsurans. 8 isolates were of T. mentagrophytes. Conclusions: In present study mixed infections of tinea cruris with corporis was the predominant clinical presentation and T. rubrum was the most common dermatophyte isolated.